2004
DOI: 10.1007/s00213-003-1628-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol effects on human risk taking

Abstract: Acute alcohol administration can produce measurable changes in human risk-taking under laboratory conditions. Shifts in trial-by-trial response probabilities suggest insensitivity to past rewards and more recent losses when intoxicated, an outcome consistent with previous studies. This shift in sensitivity to consequences is a possible mechanism in alcohol-induced changes in risk taking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 61 publications
7
128
4
2
Order By: Relevance
“…Moreover, few studies have examined the dosedependent effects of alcohol on risky behaviour, suggesting a linear relationship (Lane et al, 2003); risk-taking behaviour rises in line with increasing alcohol dose. Namely, gambles appear riskier with a BAC of .08% compared to .02, .04, and .05% (Bidwell et al, 2013;Lane et al, 2004), and participants are found to drive riskier at .08% BAC, than .05%. However, the findings in this area are inconsistent and other studies have found no difference in alcohol's effects between varying BAC (Berthelon & Gineyt, 2014;M.…”
Section: Whisky To Riskymentioning
confidence: 93%
See 4 more Smart Citations
“…Moreover, few studies have examined the dosedependent effects of alcohol on risky behaviour, suggesting a linear relationship (Lane et al, 2003); risk-taking behaviour rises in line with increasing alcohol dose. Namely, gambles appear riskier with a BAC of .08% compared to .02, .04, and .05% (Bidwell et al, 2013;Lane et al, 2004), and participants are found to drive riskier at .08% BAC, than .05%. However, the findings in this area are inconsistent and other studies have found no difference in alcohol's effects between varying BAC (Berthelon & Gineyt, 2014;M.…”
Section: Whisky To Riskymentioning
confidence: 93%
“…In line with previous research conducted on individuals in isolation (c.f., George et al, 2005;Lane et al, 2004) findings illustrate an increase in risky decisions following alcohol consumption, compared to a soft drink. However, when comparing decisions made by groups with those by isolated individuals in a later study , an alcohol-induced increase in risk-taking behaviour was only found in those who were tested in groups relative to intoxicated individuals making the decision in isolation.…”
Section: Social Influences and Alcohol Effects On Risky Behaviourmentioning
confidence: 96%
See 3 more Smart Citations